2023
DOI: 10.1200/jco.22.01797
|View full text |Cite
|
Sign up to set email alerts
|

Brexucabtagene Autoleucel for Relapsed or Refractory Mantle Cell Lymphoma in Standard-of-Care Practice: Results From the US Lymphoma CAR T Consortium

Abstract: PURPOSE Brexucabtagene autoleucel (brexu-cel) is an autologous CD19-directed chimeric antigen receptor (CAR) T-cell therapy approved for relapsed/refractory mantle cell lymphoma (MCL). This therapy was approved on the basis of the single-arm phase II ZUMA-2 trial, which showed best overall and complete response rates of 91% and 68%, respectively. We report clinical outcomes with brexu-cel in the standard-of-care setting for the approved indication. PATIENTS AND METHODS Patients who underwent leukapheresis betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 38 publications
4
56
3
1
Order By: Relevance
“…As in the recent US Lymphoma CAR T Consortium retrospective study of brexu-cel, 9 we found that CAR T-cell therapy was effective in heavily pre-treated, refractory patients (4 median lines of prior therapy in our cohort; 90% with POD24). The systemic disease CR rate in our cohort of 90% (9/10) is comparable to the 82% reported in the consortium study 9 and the 68% reported in ZUMA-2. 7 Likewise, durable disease control was similar with a 12-month PFS in our cohort of 47% compared to 59% in the recently published real-world cohort 9 and 61% in ZUMA-2.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As in the recent US Lymphoma CAR T Consortium retrospective study of brexu-cel, 9 we found that CAR T-cell therapy was effective in heavily pre-treated, refractory patients (4 median lines of prior therapy in our cohort; 90% with POD24). The systemic disease CR rate in our cohort of 90% (9/10) is comparable to the 82% reported in the consortium study 9 and the 68% reported in ZUMA-2. 7 Likewise, durable disease control was similar with a 12-month PFS in our cohort of 47% compared to 59% in the recently published real-world cohort 9 and 61% in ZUMA-2.…”
Section: Discussionsupporting
confidence: 77%
“…In these patients, CAR T-cell therapy was feasible with a similar toxicity profile compared to that observed for patients without CNS involvement. 8,9 However, given the limited number of patients reported, additional data are needed to confirm these findings and guide clinical management for this uncommon patient subgroup. In this retrospective study, we report the efficacy and safety of anti-CD19 CAR T-cell therapy in 10 patients from three US academic centres with MCL and SCNS involvement.…”
Section: Introductionmentioning
confidence: 99%
“…20 The 6-month PFS was 69%, and 12-month PFS was 59%. 20 RW patients could receive bridging therapy ranging from venetoclax to radiation whereas patients in the ZUMA-2 study could only receive BTKi or corticosteroids. The difference in bridging therapy could account for the different CR rates in RW patients compared to patients from registration trials.…”
Section: Real-world Datamentioning
confidence: 93%
“…Similarly, 168 RW patients with mantle cell lymphoma who received brexu‐cel experienced similar efficacy and toxicity when compared to patients enrolled in the ZUMA‐2 trial 20 . The 6‐month PFS was 69%, and 12‐month PFS was 59% 20 . RW patients could receive bridging therapy ranging from venetoclax to radiation whereas patients in the ZUMA‐2 study could only receive BTKi or corticosteroids.…”
Section: Current Fda Approvals Of Car‐t Therapies Across Novel Indica...mentioning
confidence: 94%
See 1 more Smart Citation